Residing at the Intersection of Theory and Practice - Suzanne Buglione (The University of Alabama, 2023)
A review of the book: Heather Coffey and Lucy Arnold. (2022). Transformative Critical Service-Learning: Theory and Practice for Engaging Community College and University Learners in Building an Activist Mindset. Myers Education Press. ISBN 978-1-975504-99-1